(untitled) (Perner’s Contacts, 2022)
The article analyzes the price development of selected commodities over the last 4 years. This is an analysis that was created to assess the behavior of prices to an unexpected price shock. Commodity markets are one of the key markets because they sell the main raw materials for the vast majority of industries. Price shocks that hit these markets thus have extensive and long-term effects on the global economy. For this reason, it is very important to monitor and analyze all price shocks and subsequently learn from the results of the analyses. One of the biggest price shocks in this century was the military conflict when the troops of the Russian Federation entered Ukraine. Both the Russian Federation and Ukraine are economies that produce a large amount of raw materials and semi-finished products for European and non-European industries. This conflict caused an upheaval in commodity markets, and not only for commodities that are produced on the territory of the affected states. The entire conflict changed the world’s logistics system. The analysis identified commodities whose prices were affected by the conflict and commodities whose prices were not significantly affected by the conflict.